Analysis of Reading Difficulties for Class III in Elementary Schools - Tia Latifatu Sadiah; Harmawati; Ayu Nurani Kosasih (LPPM Universitas Buana Perjungan Karawang, 2021)
This study aims to determine students who have difficulty reading whether it is difficulty distinguishing letters or difficulty spelling a word in grade III of Elementary School at SD Negeri Plawad VI, East Karawang. This research is a type of qualitative research. The population used in this study was 2 of the 21 total students in class III SD Negeri Plawad VI, East Karawang. This data collection technique through interviews and also the A DANA media demonstration method. Interviews were conducted with 4 respondents represented by the Principal, Teachers, Students and also Parents of Students. The data reduction analysis technique in this study is to select the main things that are in accordance with the focus of the research and the researcher uses to classify, direct and discard the data obtained by the researcher in the form of data from interviews, observations, and documentation from informants. So that it can provide a sharper picture of the results of the observations. The results of this study seem to be very helpful for students who have difficulty reading. After learning to read using the A DANA media according to the schedule applied, these students experienced changes such as easier spelling and smoother reading which was different from before.